Biomechanics of the heel pad for type 2 diabetic patients - Hsu, Tsz-Ching; Lee, Ying-Shiung; Shau, Yio-Wha (Clinical biomechanics (Bristol), 2002)
Objectives. To quantify the dynamic behavior of the heel pad in type 2 diabetic patients and age-matched healthy individuals using mathematical modeling. Background. No single parameter can fully describe the heel-pad biomechanical properties during the loading–unloading process. Design. A descriptive study using pseudoelastic modeling was conducted to simulate the heel-pad stress–strain relationship in the loaded and unloaded states. Transmission electron microscope was used to examine six heel specimens taken from amputated legs in diabetic and non-diabetic patients. Methods. Energy dissipation ratio, loading curvature, and unloading curvature were calculated from the stress–strain curve-fits. Differences in ultrastructure between the heel pad of healthy subjects and those with diabetes were described. Results. The diabetic patients had a significantly higher mean energy dissipation ratio (mean 36.1% (SD, 8.7%) vs mean 27.9% (SD, 6.1%); P<0.001) and mean unloaded curvatures (mean 11.8 (SD, 5.1) vs mean 8.46 (SD, 2.6); P<0.001) than those of the control group. The collagen fibrils in diabetic heel samples were ruptured with unclear striation and uneven distribution. Conclusions. The curvature parameters may explain the poor rebound phenomenon resulting in the high impact energy in diabetic heel pads. Breakdown in collagen fibrils may be responsible for this observation. Relevance These findings can be integrated into the fabrication of orthotics that dissipate excessive heel impact energy and protect against injury.